Rugometric and microtopographic inspection of theet' enamel - Costa, Manuel F. M. (2013)
The roughness of teeth’ enamel is an important parameter in orthodontics. One example is the application in the process of decreasing tooth-size by reducing the interproximal enamel surfaces (stripping) of teeth. In order to achieve smooth surfaces clinicians have been testing various methods and progressively improved this therapeutic technique. The evaluation the surface roughness following teeth interproximal reduction is fundamental in the process. In general tooth’ surface is not flat presenting a variety of complex geometries. In this communication we will report on the metrological procedure employed on the rugometric and microtopographic inspection by optical active triangulation of raw and processed (interproximal stripping) tooth surfaces.